Dielectric Strength And Viscosity Of Palm Oil Based Nanofluids For Liquid Insulation In Power Transformer - Mohamad, Mohd Safwan (2018)
The liquid insulation system of high voltage oil-immersed transformers is involved in this thesis. Until now, mineral insulation (MI) oils are typically used in high voltage oilimmersed transformers because of their excellence in dielectric strength and cooling performance. However, MI oils are non-renewable and non-sustainable sources. This has led scientists and researchers to formulate alternative insulation liquids such as natural ester insulation (NEI) oils to replace MI oils. Palm fatty acid ester (PFAE) is one of the ester types of insulation oil and the alternative oil to replace MI oils. This PFAE oil was developed in 2006 by Lion Corporation as insulation oil for transformer applications which have several advantages compared to MI oils i.e. good biodegrability, excellent performance in insulation and cooling medium. Nowadays, nanotechnology is one of the most important research fields especially in electrical insulation system due to the increasing demand for the electrical power in the world. Therefore, adding the nanoparticles is one of the approaches used by researchers to improve the performance of liquid insulation also known as nanofluids. The use of nanofluids in insulation system give more benefit in terms of insulation performance, design and power capacity of transformer. Based on this premise, the objectives of this research is to formulate PFAE oil-based nanofluids by dispersing three types of nanoparticles (i.e. conductive, semi-conductive and insulating nanoparticles) into PFAE oil. The potential of these nanofluids as insulation liquids is validated based on its Alternating Current (AC) breakdown voltage and viscosity. In sample preparation of PFAE oil-based nanofluids, four specific procedures must be followed i.e. weighing, homogenizer treatment, vacuum oven and moisture removal treatment process. The AC breakdown voltage was measured which complies with the specifications of the ASTM D1816 and the viscosity of the oil samples was measured according to ASTM D445 and ASTM D2983. The findings from the AC breakdown voltage suggested that the PFAE oil-based conductive nanofluid has the highest dielectric strength enchancement at weibull probability of 63.2 % with a value of 50.57 % relative to that for virgin PFAE oil. Besides that, the histogram for this nanofluids is skewed to the left, whereby most of the data fall within a range of 45 – 49 kV. In terms of heat transfer, the PFAE oil-based insulating nanofluid has the lowest viscosity compared to the other oil samples, particularly at 60 oC, based on viscosity values. Both of these parameters (AC breakdown voltage and viscosity) are crucial to designers of high voltage equipment and systems. In conclusion, the effects on breakdown voltage is more significant compared to the viscosity when nanoparticles are added into the PFAE oil.